Microbial strategies for drought stress mitigation- a sustainable frontier in plant resilience - Gahlot, Kumar D. (Frontiers in Plant Science, 2026)
Drought stress is a major constraint on global agriculture, exacerbated by climate change and increasing water scarcity. Conventional strategies such as breeding and genetic engineering have improved drought tolerance in crops, yet their scalability and adaptability remain limited. Microbial interventions, particularly those involving beneficial plant-associated microorganisms, offer a sustainable and complementary approach to enhance plant resilience under water-deficit conditions. This opinion article explores microbial strategies for drought mitigation, emphasizing the role of Rhizobium strains, digested distillery spent wash, and multi-omics technologies. Recent studies demonstrate that developed Rhizobium strains significantly improve soil fertility, nodulation, and nitrogen fixation in legumes, contributing to higher yields and better soil health in drought-prone regions. Similarly, the application of digested distillery spent wash in chickpea (Cicer arietinum) enhances nutrient uptake, photosynthetic activity, and drought tolerance. Advances in genomics, transcriptomics, proteomics, and metabolomics have revealed complex plant–microbe interactions, identifying microbial metabolites and signaling pathways that activate drought-responsive genes and osmo-protective mechanisms. Despite these promising findings, challenges persist in translating laboratory results to field conditions due to soil heterogeneity and microbial competition. Precision microbiome engineering, informed by multi-omics data, and the development of tailored microbial consortia represent a transformative frontier for sustainable agriculture. By integrating ecological complexity with technological innovation, microbial strategies can reduce chemical inputs, promote regenerative practices, and build resilient agroecosystems. This article advocates elevating microbes from supporting roles to central players in addressing drought stress and ensuring global food security.